ICT Based Agro-Advisory Services in Nepal - Paudel, R.; Baral, P.; Lamichhane, S.; Marahatta, B. P. (Journal of the Institute of Agriculture and Animal Science, 2018)
The world has already witnessed the rapid surge in use of Information Technology (IT) in agriculture and understands its effectiveness through the miracles we have achieved. In such context, agriculture extension and advisory service in Nepal can be heavily boosted with the help of most effective and affordable information and communication technologies (ICTs). With smart phones, internet services, mobile networks, televisions and radio widespread all over the country, they can prove to be a promising means for dissipation of information in rapidly altering and modernizing farming system of Nepal. This paper aims to explore the current scenario, role and effectiveness of ICTs in agro-advisory services of Nepal and to point out salient issues hampering the development of ICT. Information and findings are based on available literature, articles and publications and they suggest that ICTs can play a crucial role in linking extension, research and farmers and in the overall development of agriculture especially in the context of developing country like Nepal. The potential contribution of ICT in agriculture extension is still fully unexplored and they can be effective means for providing timely and relevant information to farmers residing in every corner of the country.